Preoperative Predictors of round window visibility on High resolution CT-scan temporal bone in patients undergoing cochlear implant surgery: A Systematic Review - Syed Akbar Abbas; Muhammad Wasif; Abdul Basit Shah Vardag; Haissan Iftikhar; Huzaifa Moiz; Syed Shabbir Afzal (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the correlation of high-resolution computed tomography-based radiological predictors with the surgical ease of access to the round window membrane in cochlear implant surgery. Method: The systematic review was conducted from April 2020 to May 2020 at the Aga Khan University Hospital, Karachi, and comprised literature search on PubMed, Cumulative Index of Nursing and Allied Health Literature- Plus, Wiley Cochrane Library and Web of Science databases for studies published in the English language between January 2000 and January 2020 that followed the population-intervention-comparison-outcome model. The search was done using key words, such as high-resolution computed tomography, temporal bone, round window and cochleostomy. Studies dealing with paediatric and adult cochlear implantations were included. The included studies were subjected to risk-ofbias assessment using the National Institute of Health study quality assessment tool for case series. The review was duly registered with PROSPERO. Results: Of the 292 studies initially identified, 6(2%) were included for systematic review. Overall patient age ranged between 1-85 years. No significant use of facial recess width for defining intraoperative visibility could be found. The use of the distance between the round window and the facial nerve, the alpha angle, the angle beta and the prediction line were of significance. Conclusion: Radiological facial recess width had no significant use in determining the ease of access to the round window membrane. Keywords: Cochlear implants, Temporal bone, Round window, Middle ear, CT scan temporal bone. PROSPERO ID registration link: https://www.crd.york. ac.uk/PROSPERO/view/CRD420261302451.